Myocarditis in children.Etiology. Pathogenesis. Epidemiology. Clinical presentation - Elena S. Vasichkina; Larisa A. Balykova; Elena N. Basargina; Loudmila V. Bregel; Elena A. Degtyareva; Igor A. Kovalev; Natalia P. Kotlukova; Irina V. Leontieva; Lyudmila V. Yakovleva; Olga S. Groznova (Педиатрическая фармакология, 2024)
Readers will be presented with a series of articles on myocarditis in children, which are based on clinical guidelines developed by a group of authors on this topic. Myocarditis is an inflammatory myocardial disease characterized by a wide range of clinical manifestations — from minor to sudden cardiac death. Given the absence of pathognomonic symptoms, as well as the similarity of manifestations in the onset with common childhood diseases such as respiratory distress, gastrointestinal diseases, infectious pathology, specialists often overlook the likelihood of a diagnosis of “myocarditis”, which causes a late start of therapy and an adverse outcome. Considering that myocarditis accounts for 12% of cases of sudden cardiac death in adolescents and young adults, suspicion of this disease in differential diagnosis in children with nonspecific symptoms and disease progression may be the key to the formation of a proper treatment strategy. Despite significant advances in the study of myocarditis in both adults and children, there are still many unresolved issues. The purpose of this article is to highlight the current view of the etiology, pathogenesis, epidemiology and clinical features in children with various types of myocarditis in order to increase the knowledge of practitioners for better clinical management of patients with myocarditis.